THE USE OF VIDEO MEDIA IN LEARNING ISLAMIC RELIGIOUS EDUCATION AND CHARACTER SUBJECTS AT STATE ELEMENTARY SCHOOL 040447 KABANJAHE - Siti Astari Litami Damanik (CV. Asry Persada Quality, 2024)
The background of this study is that the use of learning media is the most influential component in the implementation of the learning process, in reality there are still many educators who carry out learning without the help of learning media including Islamic Religious Education teachers at elementary, middle, and high school levels. Likewise at SD Negeri 040447 Kabanjahe, Islamic Religious Education and Character Education subject teachers also use traditional media. In learning, the use of video media is still very minimal (PAI Subject Teacher at SD Negeri 040447 Kabanjahe, 2024). Therefore, the researcher intends to find out the causes of the less than optimal use of video learning media. The purpose of this study was to find out how to use video media in learning Islamic Religious Education and Character Education subjects at SD Negeri 040447 Kabanjahe. In addition, identifying the advantages and disadvantages of learning Islamic Religious Education and Character Education using video media. The research method used is a qualitative method with a descriptive analysis approach. This type of research is field research. Data collection was carried out through interviews, observations and documentation. Then data analysis was carried out by condensing data, presenting data and drawing conclusions. This study involved the principal, teachers and several grade VI students at SD Negeri 040447 Kabanjahe